Students Career Readiness: Issues and Evidence from Mawuko Girls Senior High School in Ho Municipality - Paul Kobina Annan Bedu-Addo; Mary Braimah; Dogbey Alice Emmanuella (Integrated Journal for Research in Arts and Humanities, 2022)
The purpose of the study was to examine the issues and evidence of the career readiness of students in Mawako Girls in the Ho Municipality. Utilizing an explanatory sequential mixed method research design, a sample of one hundred and thirty students of Mawuko Girls Senior High School and ten teachers, from a population of 484, (comprising of 412 students and 72 teachers) was used for the study. A self-developed questionnaire (α 0.85) was used for students’ data collection, and an interview guide for teachers. The study was guided by four research questions. Percentages and weighted means were used to analyse the quantitative data, while thematic analysis was utilized to analyse the quantitative data. The findings of the study revealed the following: That student in Mawako Girls have good level of career awareness. Additionally, students acquire information on career from the school. electronic media, newspapers, magazines, teachers, and friends. Finally, students are faced with four major challenges as they make their career choices namely: lack of funds to pursue required courses for the job they want to do in future, lack of the required information for career choice-making; acceeding to the career choice preferred by parents and guardians; and finally lack teachers to teach required subjects for students’ preferred careers. The study recommends that: The headmaster of the school should insist that students receive career guidance once they are admitted into the school. The school's library should be furnished with adequate magazines and newspapers since students read them for various information including that of their career choices. The school should be connected to the World Wide Web, to create a good source for educating pupils with career information. Finally, the school's computer laboratory must be adequately resourced with internet connection and computers to allow students to independently search for information on careers.